El Excentrico, 1972-05-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 20, 1972 [20 de mayo de 1972]. No volume or issue number. Cover has photograh of Don Cortese, running for supervisor in District 2.